Heterozygous carriers of classical homocystinuria tend to have higher fasting serum homocysteine concentrations than non-carriers in the presence of folate deficiency. Issue 6 (December 2015) - Lu, Yung-Hsiu; Cheng, Li-Mei; Huang, Yu-Hsiu; Lo, Ming-Yu; Wu, Tina Jui-Ting; Lin, Hsiang-Yu; Hsu, Ting-Rong; Niu, Dau-Ming
Summary: Background & aims: Many studies have reported that serum total homocysteine (tHcy) levels in cystathionine-beta-synthase (CBS) carriers are usually normal and only elevated after a methionine load. However, the amount of methionine required for a loading test is non-physiological and is never reached with regular feeding. Therefore, CBS carriers do not seem to be at an increased risk of cardiovascular diseases. However, the risk of cardiovascular diseases of CBS carriers with folate deficiency has not been studied. We recently found an extraordinarily high carrier rate (1/7.78) of a novel CBS mutation (p.D47E, c.T141A) in an Austronesian Taiwanese Tao tribe who live in a geographic area with folate deficiency. We evaluated if the CBS carriers tend to have higher fasting serum tHcy concentrations than non-carriers in presence of folate deficiency. Methods: The serum tHcy and folate levels before and after folate replacement were measured in 48 adult Tao carriers, 40 age-matched Tao non-carriers and 40 age-matched Han Taiwanese controls. Results: The serum tHcy level of the Tao CBS carriers (17.9 ± 3.8 μmol/l) was significantly higher than in Tao non-carriers (15.7 ± 3.5 μmol/l; p < 0.008) and Taiwanese controls (11.8 ± 2.9 μmol/l; p < 0.001). Furthermore, a high prevalence of folate deficiency in the Tao compared with the Taiwanese controls (4.9 ± 1.8 ng/ml vs. 10.6 ± 5.5 ng/ml; p < 0.001) was also noted. Of note, the difference in tHcy levels between the carriers and non-carriers was eliminated by folate supplementation. (carriers:13.65 ± 2.13 μmol/l; non-carriers:12.39 ± 3.25 μmol/l, p = 0.321). Conclusions: CBS carriers tend to have a higher tHcy level in the presence of folate deficiency than non-carriers. Although many reports have indicated that CBS carriers are not associated with cardiovascular disease, the risk for CBS carriers with folate deficiency has not been well studied. Owing to a significantly elevated level of fasting tHcy without methionine loading, it is important to evaluate the risk of cardiovascular disease in CBS carriers with folate deficiency.